Leukocyte function and health status of calves supplemented with vitamins A and E - Eicher-Pruiett, S. D.; Morrill, J. L.; Blecha, Frank; Chitko-McKown, C. G.; Anderson, N. V. (Kansas Agricultural Experiment Station, 2011)
Forty-four Holstein calves were fed milk replacers with varied concentrations of vitamins A and E from 3 to 45 d of age to determine their effects on concentrations of plasma vitamin A (retinol and retinyl palmitate) and vitamin E (a- tocopherol), lymphocyte and neutrophil functions, and health of calves. Plasma a-tocopherol was unaffected by increased vitamin A supplementation. Fecal scores, and eye and nose membrane responses were improved with increased vitamin A and lower vitamin E concentration, whereas the same treatment tended to reduce neutrophil cytotoxic and bactericidal activity by 6 wk of age. Increased supplemental vitamin E tended to enhance neutrophil functions. However, age appeared to have an effect on response to both vitamins.
Keywords: Dairy; Calves; Leukocytes; Vitamins; Health